Effectiveness of disinfectants against methicillin resistant Staphylococcus aureus (MRSA) contamination in hospital: a review - Arviansyah; Herman Yosef Limpat Wihastyoko; Yudi Siswanto; Wilma Agustina; Elisabeth Prajanti Sintaningrum; Eka Nugraha Prima; Michelle Gunawan; Dewangga Yudisthira (Published by Universitas Gadjah Mada, 2025)
Methicillin-resistant Staphylococcus aureus (MRSA) contamination is still widely reported in various hospital areas. Despite routine cleaning and preventive measures in places such as hospitals, the prevalence of MRSA is still increasing worldwide, especially in Asia. This review aimed to evaluate the effectiveness of disinfectants against MRSA contamination in hospitals. Articles were searched from PubMed, ScienceDirect, Cochrane, and Google Scholar databases using specific keywords and boolean operators. Journal selection from these databases was based on inclusion criteria, exclusion criteria, and PICOS framework. Studies that did not fit the topic or study design and had paid access and duplication were excluded. A total of five valid and reliable articles found that some disinfectants, such as JUC Polymer, a combination of hydrogen peroxide (H2O2) and silver cations (Ag), have effectiveness in eradicating germs or inhibiting the growth of MRSA germs. The application of disinfectants in MRSA also showed benefits in terms of cost. However, the use of disinfectants needs to be considered because they can cause tolerance and resistance. In conclusion, MRSA disinfectants are still proven effective with various methods and precautions. In addition, disinfectants are beneficial in terms of prevention and health financing.